Performing pull-ups with small climbing holds influences grip and biomechanical arm action - Vigouroux, L.; Devise, M.; Cartier, T; Aubert, C.; Berton, E. (Journal of Sports Sciences, 2019)
Pull-ups are often used by sport-climbers and other athletes to train their arm and back muscle capabilities. Sport-climbers use different types of holds to reinforce finger strength concomitantly. However, the effect of grip types on pull-up performance had not previously been investigated. A vertical force platform sensor measured the force exerted by climbers when performing pull-ups under six different grip conditions (gym-bar, large climbing hold, and four small climbing holds: 22mm, 18mm, 14mm, and 10mm). The electromyography of finger flexors and extensor muscles were recorded simultaneously. The maximal arm power and summed mechanical work were computed. The results revealed that the number of pull-ups, maximal power, and summed mechanical work decreased significantly with the size of the climbing hold used, even if no differences were found between a large climbing hold and a gym-bar. Electromyography of the forearm muscles revealed that the use of a climbing hold generated finger flexor fatigue and that the level of cocontraction was impacted by the different segment coordination strategies generated during the pull-ups. These findings are likely to be useful for quantifying training loads more accurately and designing training exercises and programs